The Effect of Obesity, Smoking Habits, and Hypertension on the Risk of Chronic Kidney Disease: A Case Control Study - Ariyanti, Rea; Rahayu, Eka Putri (Panakeia Journal of Epidemiology, 2024)
Chronic Kidney Disease (CKD) is a global public health problem with increasing prevalence and incidence of kidney failure. About 1 in 10 of the global population experiences chronic kidney failure at some stage. There are several risk factors that are thought to increase the incidence of chronic kidney disease, such as obesity, smoking habits and hypertension. This study aims to determine the influence of obesity, smoking habits and hypertension on the risk of chronic kidney disease. The research design is case control. The research was carried out at Panti Nirmala Hospital Malang with a sample size of 286 respondents, consisting of 143 case groups and 143 controls. Data analysis used the chi-square test. The results of the study showed that hypertension status (p=0.014) had a significant influence on the incidence of chronic kidney disease, while other variables such as obesity (p=0.122) and smoking habits (p=0.077) were not proven to have an influence in causing chronic kidney disease. In the case group, it was discovered that more than half of the respondents stated that they had a smoking habit and suffered from hypertension. It is recommended that people carry out regular health checks and change their lifestyle by not smoking and always controlling their blood pressure to keep it normal.